Sketchy - Samms, Olivia (Bea Catcher chronicles, 2013)
The first book in a series about 17 year old Bea Washington, an edgy, charismatic outsider and recovering addict, who discovers that with her newfound sobriety, she has a disturbing new skill: an ability to see, and draw, people's thoughts. Alarmingly, these visions are only getting stronger and increasing in frequency. As another girl in school is raped and left for dead, Bea must come to terms with her talent, learn to face her own truth, and try to help identify and stop the killer before he strikes again.